2000
DOI: 10.1007/s11883-000-0062-8
|View full text |Cite
|
Sign up to set email alerts
|

Hormone replacement therapy in the prevention and treatment of atherosclerosis

Abstract: As the population ages, the increasing number of women at risk for cardiovascular disease represents both a potential crisis and an opportunity in healthcare management. Although the overall death rate from cardiovascular disease in the general population is decreasing, the absolute numbers for women are increasing. A reduction in modifiable risk factors in women must be aggressively pursued by clinicians and health systems. Menopause is associated with many adverse effects on cardiovascular-disease risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…Indeed, because of possible serious flaws in the study, a protective benefit of HRT for secondary CVD prevention cannot be ruled out.” Some articles were ghostwritten (see Table S1). For example, a 2000 article authored by Mosca [51] states, “Remarkable consistency among epidemiologic studies supports a cardioprotective role of ERT.”…”
Section: Messagingmentioning
confidence: 99%
“…Indeed, because of possible serious flaws in the study, a protective benefit of HRT for secondary CVD prevention cannot be ruled out.” Some articles were ghostwritten (see Table S1). For example, a 2000 article authored by Mosca [51] states, “Remarkable consistency among epidemiologic studies supports a cardioprotective role of ERT.”…”
Section: Messagingmentioning
confidence: 99%
“…HDL-C participates in transferring and eliminating lipid so as to protect the cardiovascular system. It has been reported that the use of estrogen in postmenopausal women could decrease the levels of TC and LDL-C and increase those of HDL-C and TG (Mosca, 2000;Lobo et al, 2001). The present study demonstrated that the levels of TG and TC decreased significantly after administration of Herba Epimedii water extract, although LDL-C and HDL-C did not change significantly.…”
Section: Discussionmentioning
confidence: 99%
“…CHD is a major cause of mobility and mortality in women,89 and the incidence of CHD increases after menopause 81011. Previous observational studies have suggested that there are long-term benefits of menopausal hormone therapy (MHT) for reducing the risk1213 or mortality141516 associated with CHD. Recently, a timing hypothesis has been raised.…”
Section: Introductionmentioning
confidence: 99%